2022
DOI: 10.1055/s-0042-1749666
|View full text |Cite
|
Sign up to set email alerts
|

Association between SARS-CoV-2 Infection and Adverse Perinatal Outcomes in a Large Health Maintenance Organization

Abstract: Objective This study aimed to examine whether severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection during pregnancy is associated with increased odds of perinatal complications and viral transmission to the infant. Study Design A retrospective cohort study of women who delivered at Kaiser Permanente Southern California hospitals (April 6, 2020–February 28, 2021) was performed using data extracted from electronic health records (EHRs). During this time polymerize chain reaction (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Since the COVID-19 pandemic, there has been data to suggest a link between SARS-CoV-2 infection in pregnancy and an increased risk of developing pre-eclampsia. Some systematic reviews found an increase in risk when collating data from different cohorts 106,107 ; however, other studies have reported that COVID-19 infection during pregnancy does not increase the risk of pre-eclampsia [108][109][110] . Pre-eclampsia is more likely to be associated with severe COVID-19, although whether one is causal of the other has not been definitively proven 107,111 .…”
Section: Maternal Agementioning
confidence: 99%
“…Since the COVID-19 pandemic, there has been data to suggest a link between SARS-CoV-2 infection in pregnancy and an increased risk of developing pre-eclampsia. Some systematic reviews found an increase in risk when collating data from different cohorts 106,107 ; however, other studies have reported that COVID-19 infection during pregnancy does not increase the risk of pre-eclampsia [108][109][110] . Pre-eclampsia is more likely to be associated with severe COVID-19, although whether one is causal of the other has not been definitively proven 107,111 .…”
Section: Maternal Agementioning
confidence: 99%
“…However, other studies have identified that the association between COVID-19 during pregnancy and adverse maternal or fetal/neonatal outcomes occurs independent of the severity of COVID-19 [3,25]. Despite recently published studies disagreeing with obstetric and neonatal complications, our study was carried out in the first and second waves of COVID-19, only with normal-risk pregnant women [26,27].…”
Section: Resultsmentioning
confidence: 89%
“…Obstetricians should be aware of prenatal follow-up of infected pregnant and possible associated perinatal complications for better planning with neonatologist for save delivery. 9 This report might help neonatologists, pediatric surgeons, and pediatric pulmonologists to understand the clinical presentation of neonatal COVID-19 and best practices for better management. Limitation of this report was lack of similar cases in literature to be reviewed.…”
Section: Discussionmentioning
confidence: 99%